1990
DOI: 10.1111/j.1528-1157.1990.tb05376.x
|View full text |Cite
|
Sign up to set email alerts
|

Psychopathology and Limbic Epilepsy: Relationship to Seizure Variables and Neuropsychological Function

Abstract: Correlations were sought among psychopathologic, neuropsychological, and seizure variables in 21 patients with limbic epilepsy. Observer-based assessments, such as the Bear-Fedio Inventory, and self-report assessments of psychopathology were used. Self-reported psychotic experiences were associated with increased seizure frequency. Increased religiosity was noted in patients whose epileptic focus included the left side. Increased neuropsychological impairment was associated with several measures of psychopatho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0
2

Year Published

1990
1990
2014
2014

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 26 publications
(24 reference statements)
0
8
0
2
Order By: Relevance
“…Studies in adults (Csernansky, Leiderman, Mandbach, & Moses, 1990; Slater & Beard, 1963) and children (Caplan, Guthrie, Shields, & Mori, 1992a; Caplan et al., 1997) have demonstrated that formal thought disorder is found in patients with complex partial seizure disorder (CPS). Evidence for a schizophrenia‐like psychosis in temporal lobe epilepsy (Caplan, Shields, Mori, & Yodoven, 1991; Lindsay, Ounsted, & Richards, 1979; Mellers, Toone, & Lishman, 2000; Schmitz, Robertson, & Trimble, 1999) and involvement of the temporal lobe in the thought disorder of schizophrenic adults (Holinger et al., 1999; Shenton et al., 1992) led us to investigate if these social communication deficits occur specifically in children with CPS and focal temporal involvement compared to children with primary generalized epilepsy with absences (i.e., petit mal) (PGE).…”
Section: Social Communication Measures: Definitions and Examplesmentioning
confidence: 99%
“…Studies in adults (Csernansky, Leiderman, Mandbach, & Moses, 1990; Slater & Beard, 1963) and children (Caplan, Guthrie, Shields, & Mori, 1992a; Caplan et al., 1997) have demonstrated that formal thought disorder is found in patients with complex partial seizure disorder (CPS). Evidence for a schizophrenia‐like psychosis in temporal lobe epilepsy (Caplan, Shields, Mori, & Yodoven, 1991; Lindsay, Ounsted, & Richards, 1979; Mellers, Toone, & Lishman, 2000; Schmitz, Robertson, & Trimble, 1999) and involvement of the temporal lobe in the thought disorder of schizophrenic adults (Holinger et al., 1999; Shenton et al., 1992) led us to investigate if these social communication deficits occur specifically in children with CPS and focal temporal involvement compared to children with primary generalized epilepsy with absences (i.e., petit mal) (PGE).…”
Section: Social Communication Measures: Definitions and Examplesmentioning
confidence: 99%
“…Waxman & Geschwind, 1975+ Bear & Fedio, 1977+ Bear, 1979+ Bear et al, 1982 + review by Csernansky et al, 1990 + review by Saver & Rabin, 1997+ Wuerfel et al, 2004+ MacDonald & Holland, 2002+ Morneau et al, 1996+ Persinger, 1984+ Diduca & Joseph, 1997+ White et al, 1995+ Feldman & Rust, 1989+ Peters et al, 1999+ Spencer, 1975+ Fenwick et al, 1985+ Cothran & Harvey, 1986 (b) Not all people with psychopathological disorders have religious experience.…”
Section: Variations Of One Religious Experience Versus a Continuum Ofmentioning
confidence: 99%
“…A description of the methods for patient selection, psychopathology, and neuropsychological assessment may be found in our companion article (Csernansky et al, 1990). Of the 21 patients, all females were excluded during analysis of neuroendocrine variables.…”
Section: Subjectsmentioning
confidence: 99%
“…A large literature exists on the question of the existence and specific nature of limbic epilepsyassociated psychopathology. In a companion study, we examined correlational relationships between seizure variables and several psychiatric and neuropsychological measures (Csernansky et al, 1990). Because the neuroendocrine aspects of limbic epilepsy are increasingly under investigation, the present correlational study of neuroendocrine, psychiatric, and neuropsychologic variables seems timely.…”
mentioning
confidence: 99%